The 'Tricky Dance' of Advocacy: A Study of Non-legal Mental Health Advocacy - Bennetts, W; Maylea, C; McKenna, Brian; Makregiorgos, H (Northumbria University Library, 2018)
Advocacy in compulsory mental health settings is complex and contested, incorporating legal, non-legal, representational and best interests advocacy. This paper presents an approach to non-legal representational advocacy used by Independent Mental Health Advocacy (IMHA), in Victoria, Australia, drawing on in-depth qualitative interviews with advocates and other key stakeholders. After outlining the Victorian context and the IMHA model, this paper shows how IMHA privileges the consumer voice using representational advocacy, which is rights-based and works for systemic change. Using a supported decision-making model, the paper highlights the enablers and challenges which exist, before discussing the implications in terms of rights, power, capacity building and systemic change. The participants saw IMHA as working to address one of the most troubling tensions in mental health care, between the perceived need for coercion and the need to support people to make their own decisions. Representational advocacy provides a clear, easily transferable and tested framework for engaging in supported decision-making processes with people in the mental health system.
Keywords: IMHA; Independent Mental Health Advocacy; Mental health; Advocacy; Victoria Australia; Non-legal advocacy; Compulsory treatment; Involuntary treatment; Supported decision-making